Can the Media Help Science? - Pollack, Henry N. (Skeptic, 2003)
Focuses on the role of mass media to promote scientific understanding. Form of publication of research result in peer-reviewed scientific journals; Accessibility of complex scientific issues to non-academic audiences; Positive consequences from a close working relationship between science and the media.